Effects of daphnetin on biofilm formation and motility of pseudomonas aeruginosa - Ye, Zuoji; Ye, Liumei; Li, Dingbin; Lin, Shunsheng; Deng, Wusheng; Zhang, Li; Liang, Jinhua; Li, Jinlong; Wei, Qingjun; Wang, Ke (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Pseudomonas aeruginosa is a common clinical opportunistic pathogen. Antibiotic resistance of P. aeruginosa is frequent, and it affects the clinical curative effect and leads to recurrent infections, disease progression, and difficult treatment, especially in cystic fibrosis patients. The drug-resistance mechanism of P. aeruginosa is complex, and biofilms play an important role. Given the widespread antibiotic resistance of P. aeruginosa, the discovery of a drug that can prevent or eradicate biofilm formation is imperative. Daphnetin (DAP), a coumarin derivative, is a safe, non-toxic, natural compound with antibacterial and anti-biofilm properties. Herein, this study highlights the bacterial motility effects, antibacterial effect, pyocyanin production, and anti-biofilm potential of DAP against P. aeruginosa. Methods In this study, the minimal inhibitory concentration of DAP against P. aeruginosa was determined using the microdilution method. The antibiofilm activity of DAP against P. aeruginosa was determined using crystal violet staining, colony-forming unit enumeration, and scanning electron microscopy. The effect of DAP on P. aeruginosa motility was detected using the swimming, swarming, and twitching agar plates to measure the diameter of the concentric area. Results We found that DAP at concentrations of 0.445–1.781 mg/mL and 0.89–1.781 mg/mL can effectively inhibit biofilm formation and eradicate the formed biofilm of P. aeruginosa, respectively. DAP reduced pyocyanin production and inhibited bacterial motility of P. aeruginosa. Discussion In conclusion, our results support the conclusion that DAP can effectively eradicate formed biofilm and inhibit biofilm formation, bacterial motility, and pyocyanin production of P. aeruginosa and may represent a natural anti-biofilm therapeutic agent.